Computed Tomography Simulation Software - Noor Hidayah, Jaafar (Universiti Malaysia Perlis, 2010)
Engineering Invention & Innovation Exhibition (ENVEX 2010) organized by Student Affairs & Alumni Department (HEPA), Universiti Malaysia Perlis (UniMAP) with collaboration Ministry of Higher Education Malaysia (MOHE) and Ministry of Science & Technology Innovation (MOSTI), 2nd - 4th April 2010 at Khoon Aik Hall, Kangar, Perlis.